Gen Z and Millennials Behavioural Intention towards Mobile Social Media Advertising in Kathmandu Valley (Quest Journal of Management and Social Sciences, 2026)
Background: Mobile social media advertising has become an important marketing tool as the use of smartphones and social media platforms continues to grow among younger generations. In Kathmandu Valley, businesses increasingly rely on mobile advertisements to reach Gen Z and Millennials, making it important to understand their perceptions, attitudes, and behavioral intentions toward such advertising.Purpose: The purpose of this study is to understand the adaptation of mobile social media advertising on consumer behavioral intention and identify effective marketing strategies that businesses can use to achieve their marketing goals.Design/methodology /approach: This study adopts an explanatory research design based on the Mobile Technology Acceptance Model. A total of 406 respondents were selected using a non-probability sampling technique, specifically convenience sampling. The data collected was analyzed using both descriptive and inferential statistical methods.Findings: The findings indicate almost equal participation of male and female respondents, most of whom have tertiary education. The major issues identified include the use of ad-blocking software and ad fatigue. Respondents also suggested the importance of proper planning, strategic advertising approaches, and stronger safety and security measures.Conclusion: The study concludes that mobile usefulness is the most influential factor affecting behavioral intention toward mobile social media advertising. Factors such as adblockers and perceived critical mass influence mobile ease of use and usefulness, which further affect behavioral intention. Additionally, homophily directly influences behavioral intention. Businesses should therefore focus on improving mobile usefulness and creating engaging, informative, and user-friendly advertising content to enhance interaction and build a loyal customer base.Keywords: Mobile social media, Digital Advertising, Behavioral intention, ad blocker